2019
DOI: 10.1111/acem.13773
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound for Confirmation of Endotracheal Tube Placement

Abstract: heading Transtracheal ultrasound can accurately guide and verify endotracheal tube placement Positive LR findings LR+: 34 for transtracheal ultrasound confirmation of endotracheal tube placement Negative LR findings LR-: 0.01 for transtracheal ultrasound confirmation of endotracheal tube placement Who was in the studies 17 studies comprising 1,595 patients, with 12 studies conducted in the ED NARRATIVEEndotracheal intubation is a common intervention in the emergency department (ED) and prehospital setting. Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…Based on the literature available till date, it is possible to recommend ultrasonography as even the first line tool for confirmation of endotracheal tube intubation compared to gold standard techniques such as end-tidal capnography, colorimetric capnography, fibreoptic bronchoscopy, direct visualization. Previous meta-analysis assessing the accuracy of ultrasonography revealed similar accuracy parameters compared to our review [48][49][50][51][52]. This shows that ultrasonography has a high amount of applicability in the clinical practice, as it has excellent performance with a very high specificity.…”
Section: Discussionsupporting
confidence: 76%
“…Based on the literature available till date, it is possible to recommend ultrasonography as even the first line tool for confirmation of endotracheal tube intubation compared to gold standard techniques such as end-tidal capnography, colorimetric capnography, fibreoptic bronchoscopy, direct visualization. Previous meta-analysis assessing the accuracy of ultrasonography revealed similar accuracy parameters compared to our review [48][49][50][51][52]. This shows that ultrasonography has a high amount of applicability in the clinical practice, as it has excellent performance with a very high specificity.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, its sensitivity and specificity vary based on operator experience and level of training. As there are studies with lesser sensitivity and specificity than our study as shown by Long et al 9 and Gottlieb et al 3 In this study adult patients were involved whose mean age was 49.6 years similar to that of study done by Abbasi, et al Majority of patients in our study were male (60.6%) similar to the study done by Chou et al 12 but was in contrast to study done by Chowdhury et al 13 The reason for this sex difference could be doctor from anesthesia department conducting study in elective patients undergoing surgery. Forty-five patients (66.2%) had bilateral equal air entry on auscultation, 14 (20.6%) had decrease air entry on left side of chest and 9 (13.2%) had decrease air entry on right side of chest during auscultation respectively.…”
Section: Discussioncontrasting
confidence: 52%
“…8 Static, grayscale imaging are common methods to visualize the location of the ETT after placement. 9 Most of the studies are done in cadavers which mimic the live scenarios. 8 Studies that are done in live patients are conducted in controlled environment like preoperative settings.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, POCUS can allow rapid confirmation during or after the intubation attempt with a relatively short training period [10,40]. Among adults, POCUS is 99% sensitive and 97% specific [10,41]; whereas, POCUS is 92% to 100% sensitive and 100% specific in pediatric patients [42]. Studies have reported consistent accuracy regardless of the ETT size or type of transducer (e.g., linear, curvilinear) used [43,44].…”
Section: Intubation Confirmationmentioning
confidence: 99%